Structural Analysis and Material Characterization of Silver Conductive Ink for Stretchable Electronics - Zulfiqar, Sana; Saad, Abdullah Aziz; Ahmad, Zulkifli; Yusof, Feizal; Bachok, Zuraihana (International Journal of Integrated Engineering, 2021)
Stretchable electronic systems have become more popular in various applications such as medical, fabric, flexible sensors for personalized health care, etc. There are two major parts of flexible and stretchable circuit boards that are substrate (a plastic material) and conductive ink (formulated polymer with conductive metal). According to electrical measurements, conductive ink plays a very important role in stretchable electronic equipment. The main objective of this paper is to develop a silver (Ag) based conductive ink and characterize its mechanical and electrical properties. Conductive ink is prepared by mixing an epoxy resin, cross – linking agent, additives (adhesion promoter), organic solvent, catalyst and silver flakes all together. ASTM D412 Type C dog bone shaped cutter is used to make three samples of conductive ink. The stress-strain analysis of conductive ink is carried out using universal testing machine (UTM). The conductivity is measured using two-point probe digital multi-meter. Also, the microstructural analysis, morphology and characterization are done by scanning electron microscopy (SEM). The images are taken after curing and tensile testing. The formulated ink possesses high conductivity and stretchability up to 137% strain. The achieved conductivity of the ink is 4.167×104 S/m. The maximum stress before failure, yield stress, Young’s and tangent moduli are calculated as 1.195 MPa, 0.86 MPa, 5.72 MPa and 2.08 MPa, respectively. The SEM analysis indicates that the distribution of silver particles is uniform and in a good density throughout the sample.